China's Emerging Regional Trade Policy - Zhao, Longyue; Malouche, Mariem; Newfarmer, Richard (2012)
The purpose of this paper is to provide a timely review and analysis of China's regional trade agreements, its motivations, and its economic implications for Association of Southeast Asian Nations (ASEAN)-China Free Trade Agreement (ACFTA) member countries and other trading partners. The paper uses the SMART model of the World Integrated Trade Solution to quantify the economic implications of the ACFTA on merchandise trade flows among member countries and other trading partners. Then, for comparative purposes, the impact of two possible paths beyond the ACFTA is simulated: an East Asia Free Trade Agreement (EAFTA) and the possible Doha Round multilateral trade liberalization. The paper finds that, if regional and bilateral trade arrangement (RTA) were only concentrated in tariff reductions, the impact on trade flows would be quite limited. China's trade liberalization will bring the similar impacts to ASEAN in three of the scenarios modeled. Japan and Korea would get more market access to China if an EAFTA were to become reality. Only in a multilateral liberalization would all RTA member countries and the rest of the world benefit. Three limitations are noteworthy. First, these types of models capture only static gains from trade. Second, the simulations do not include services liberalization, which could readily provide benefits in several multiples of merchandise trade, and third, it is assumed that full removal of all border barriers at once, in a multilateral scenario, would be of illuminating heuristic value but is unlikely to occur in reality. The paper demonstrates the wisdom of China's simultaneous pursuit of unilateral, regional, and multilateral liberalization--because the wider the trading group involved in the liberalization, the more China and its partners will benefit. The tariff reductions in RTAs will have limited effects on expanding merchandise trade, especially when compared with comprehensive and multilateral liberalization agreements.